Diversity and complexity: Becoming a teacher in England in 2015–2016. Issue 1 (15th February 2018) - Whiting, Caroline; Whitty, Geoff; Menter, Ian; Black, Pat; Hordern, Jim; Parfitt, Anne; Reynolds, Kate; Sorensen, Nick
Abstract : This paper is based on a profile of Initial Teacher Training (ITT) provision in England, which was developed as part of a wider research programme on Diversity in Teacher Education (DiTE) based at Bath Spa University. It provides a new topography of routes to qualified teacher status (QTS) in England for the academic year 2015–2016, along similar lines to an exercise undertaken for an earlier research programme, the ESRC funded Modes of Teacher Education (MOTE) projects conducted in the 1990s. The allocations and census data published by the National College for Teaching and Leadership (NCTL) provide the basis for this new topography, with additional material from a range of sources, mostly online. Reflections on further changes in policy discourse since the year of analysis hint at an acknowledgement of the role of Higher Education (HE) and a reduced emphasis on the much vaunted focus on 'school‐led' routes. However, there is little to reassure either ITT providers, or potential candidates, of a long term plan aimed at halting the trajectory towards over‐complexity and incoherence. The analysis raises important questions about the quality of such diverse teacher education provision, the nature of partnership between higher education institutions and schools, and the impact of reform on the identities of those training to teach.